Star Wars. 9, hope dies - Gillen, Kieron (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2018)
"A secret rebel base. A secret rebel fleet. The chance of victory... and now, Darth Vader has found it. There is no escape. When did the Empire first strike back? Here. And it struck here hardest"--Provided by publisher.